2011
DOI: 10.1309/ajcp1v3uxeiqtsle
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Beckman Coulter UniCel DxH 800, Beckman Coulter LH 780, and Abbott Diagnostics Cell-Dyn Sapphire Hematology Analyzers on Adult Specimens in a Tertiary Care Hospital

Abstract: We evaluated the new Beckman Coulter DxH 800 hematology analyzer (Beckman Coulter, Miami, FL) vs the Abbott Diagnostics Cell-Dyn Sapphire (Abbott Diagnostics, Santa Clara, CA) and Beckman Coulter LH 780 hematology analyzers using 430 adult specimens. The DxH 800 provided a CBC and differential that correlated well with those of the Sapphire and LH 780, with most parameters showing correlation coefficients (r) of more than 0.97. In the instrument vs 400-cell manual differential comparison, all 3 instruments sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 20 publications
7
33
4
1
Order By: Relevance
“…In the differential a high correlation (r>0.970) was demonstrated for NEUT, LYMP and EOS, whereas a moderate correlation (r=0.823) was found for MONO and low correlation (r=0.447) was found for BASO. These findings are equivalent to those observed for other comparisons of state-of-the-art laboratory analysers 19 20…”
Section: Discussionsupporting
confidence: 88%
“…In the differential a high correlation (r>0.970) was demonstrated for NEUT, LYMP and EOS, whereas a moderate correlation (r=0.823) was found for MONO and low correlation (r=0.447) was found for BASO. These findings are equivalent to those observed for other comparisons of state-of-the-art laboratory analysers 19 20…”
Section: Discussionsupporting
confidence: 88%
“…Whereas, the discrepancy of manual monocyte counts from those by SPC/ITC method and by the hematology analyzer requires special attention. In the literature, similar observations of discrepancy were reported for monocyte counts between manual and automated counting [17,18]. They were partly attributed to the presence of immature small monocytes, which were not counted as monocytes, or the presence of atypical lymphocytes, which were counted as monocytes.…”
Section: Overall Utility Of the Spc/itc Methods And Limitations In Difsupporting
confidence: 63%
“…Although the reference method for hemoglobinometry is spectrophotometry using hemiglobin-cyanide, cyanide-free reagents have been widely adopted for safety and environmental purpose [34, 35]. Therefore, the DxH 800 analyzer represents current standards [36, 37]. We found that hemoglobin was systematically overestimated (mean 0.8 g/dL) by the POC assay.…”
Section: Discussionmentioning
confidence: 92%